Meningiomas of the Planum Sphenoidale and Tuberculum Sella - Echalier, Elizabeth L.; Subramanian, Prem S. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Patients with meningiomas of the planum sphenoidale and tuberculum sella often present with insidious vision loss in one or both eyes as the only sign or symptom of their disease, although other sensory, oculomotor, and even endocrine abnormalities may be seen in a minority of cases. Incidentally discovered tumors also are common, as patients may undergo neuroimaging for unrelated symptoms or events. Depending on the size and orientation of the tumor, central vision loss from optic nerve compression may be a later sign, and loss of peripheral vision in one or both eyes may not be recognized until it has progressed to areas closer to fixation. A thorough neuroophthalmologic assessment including visual field testing will help to define the extent of optic pathway involvement. Both fundus examination and optical coherence tomography of the retinal nerve fiber layer and macular ganglion cell complex will aid in determining prognosis after treatment of the tumor. Orbital surgery rarely is indicated as primary therapy for meningiomas in this location, and surgical resection or debulking is usually pursued before consideration is given to radiation therapy. Because of the long-term risk of residual tumor growth or recurrence, neuroophthalmic surveillance along with serial neuroimaging is required for years after tumor resection and/or radiation therapy.
Keywords: skull base meningioma; compressive optic neuropathy; visual field defect; chiasmal syndrome; radiation therapy